Examining the Attitude-Behavior Gap and Adoption Intention of SHS Technology: The Role of Social Influence - Zefanya Alanza Christabel Loveldy; Tuan Ahmad Tuan Ismail; Sarah Siti Jubaedah (Politeknik Negeri Bandung, 2021)
Current fuel-based electricity used to fulfill household electricity needs is one of the reasons that worsen global warming. Therefore, the use of solar energy starts to be favorable. Indonesia is benefited from abundant solar radiation levels, yet the utilization of solar energy as one possible solution is still very limited. The non-optimal use of this eco-friendly energy needs to be investigated by examining consumers’ intention to adopt Solar House System (SHS) technology along with factors affecting it. This study used Behavioral Reasoning Theory (BRT) that consists of values, reasons for adoption, reasons against adoption, attitude, and social influence as variables to predict adoption intention. Further, Partial Least Square Modeling was used to test the hypotheses after collecting 428 data by distributing questionnaires in Bandung Area. The result reveals that social influence plays the most significant role in predicting SHS adoption intention, attitude, reasons for adoption, and values. Thus, this study extends our understanding of the attitude-behavior gap in the context of green technology and the impact of social influence.